Clinical research on lumbar oblique-pulling manipulation in combination with sling exercise therapy for patients with chronic nonspecific low back pain - Wang,Shang-Quan (2019)
SUMMARY OBJECTIVE: To investigate clinical curative effects of lumbar oblique-pulling manipulation in combination with sling-exercise-therapy training on chronic nonspecific lower back pain. METHODS: A total of 60 patients with chronic nonspecific lower back pain in the Outpatient Department were included in this study. These patients were randomly divided into two groups: the observation group and the control group. The control group adopted a single sling-exercise-therapy training three times a week, while the observation group adopted lumbar oblique-pulling manipulation in combination with manipulation treatment once a week. The course of treatment lasted for four weeks. RESULTS: (1) Before and after treatment, the ODI score was compared within the group. A remarkable statistical significance was observed from the third day (P<0.05). At the third month of follow-up, the difference in ODI scores between these two groups was statistically significant (P<0.05). (2) Before and after treatment, it was observed that differences in VAS scores from the third day were statistically significant (P<0.05). (3) The difference in muscle strength between these two groups had remarkable statistical significance in the third month of follow-up (P<0.05). CONCLUSION: The effective rehabilitation function of lumbar oblique-pulling manipulation in combination with sling-exercise-therapy training in patients with CNLBP is superior to that of sling-exercise-therapy training alone.